Bacillus subtilis CF-3 Volatile Organic Compounds Inhibit Monilinia fructicola Growth in Peach Fruit - Zhou, Minshun; Li, Peizhong; Wu, Shiyuan; Zhao, Pengyu; Gao, Haiyan (Frontiers in Microbiology, 2019)
In this study, we evaluated the effects of volatile organic compounds (VOCs) produced by Bacillus subtilis CF-3 in inhibiting Monilinia fructicola in vitro and in vivo. In the in vitro experiments, the effect of VOCs on the growth of the pathogenic fungi was explored by using plate enthalpy test; mycelial morphology was studied by scanning electron and transmission electron microscopy; and fatty acid contents in the cell membrane were assessed by gas chromatography-mass spectrometry (GC-MS). The results indicated that treatment with benzothiazole and CF-3 for 24 h, in the form of a fermentation broth (24hFB), significantly inhibited the germination of fungal spores, modified hyphal and cell morphology, and decreased the cell membrane fluidity and integrity. In the in vivo experiments, the effect of VOCs on the defense mechanism of peach fruit toward M. fructicola was studied, and we found that benzothiazole and CF-3 24hFB inhibited the activity of the pathogenic enzymes (pectinase, cellulase) secreted by M. fructicola to reduce the decomposition of plant tissues, activate the antioxidant enzymes (peroxidase, polyphenol oxidase, catalase, superoxide dismutase) in the fruit to eliminate excessive reactive oxygen species in order to reduce plant cell damage, and trigger disease-resistant enzymes (phenylalanine ammonia-lyase, chitinases, β-1,3-glucanase) to enhance the resistance of peach fruit to M. fructicola and inhibit its growth. This study suggests that CF-3 VOCs could activate disease-resistant enzymes to prevent the invasion of pathogenic fungi and induce resistance in peach, thereby providing a theoretical basis for future applications.